2023
DOI: 10.1021/acs.iecr.3c02857
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Role of Co and Mn Elements in Ni-Rich LiNi0.9CoxMn0.08–xAl0.02O2 Cathode Materials

Zeng Zeng,
Fuqiren Guo,
Yang Song
et al.

Abstract: Ni x Co y Mn z Al 1−x−y−z O 2 (NCMA, 1 − x − y − z ≥ 0.9) is one of the most promising cathode materials for lithium-ion batteries due to its high energy density and low cost. However, the roles of Co and Mn contents in NCMAs remain to be investigated. Herein, LiNi 0.9 Co x Mn 0.08−x Al 0.02 O 2 (x = 0.07, 0.05, 0.03) are synthesized by a hydroxide coprecipitation method and high-temperature solidphase method. The results show that Co can increase the value of the c-axis, decrease the content of Ni 2+ on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…Manganese shows a relatively persistent þ4 valence state when the nickel level is significantly higher than the manganese content (Figure 1E). 19 Zeng et al 35 investigated the mechanism of Co and Mn elements in high nickel materials. They found that the Co element can increase the Li layer spacing, enhance the migration rate of lithium ions to achieve excellent multiplicity performance, and inhibit the rapid expansion of the lattice along the c-axis during charging.…”
Section: T a B L Ementioning
confidence: 99%
See 1 more Smart Citation
“…Manganese shows a relatively persistent þ4 valence state when the nickel level is significantly higher than the manganese content (Figure 1E). 19 Zeng et al 35 investigated the mechanism of Co and Mn elements in high nickel materials. They found that the Co element can increase the Li layer spacing, enhance the migration rate of lithium ions to achieve excellent multiplicity performance, and inhibit the rapid expansion of the lattice along the c-axis during charging.…”
Section: T a B L Ementioning
confidence: 99%
“…Manganese shows a relatively persistent +4 valence state when the nickel level is significantly higher than the manganese content (Figure 1E). 19 Zeng et al 35 . investigated the mechanism of Co and Mn elements in high nickel materials.…”
Section: Introductionmentioning
confidence: 99%